1996
DOI: 10.1139/x26-024
|View full text |Cite
|
Sign up to set email alerts
|

Forest cover types derived from Landsat Thematic Mapper imagery for Changbai Mountain area of China

Abstract: The distributions of various forest cover types on Changbai Mountain of northeastern China were examined by interpreting Landsat Thematic Mapper satellite data. The area studied consists of the Changbai Nature Reserve plus an 8 km wide buffer zone. The dominant forest cover types were mixed Korean pine (Pinuskoraiensis Sieb. & Zucc.) hardwood forest below 1100 m above sea level (asl) and evergreen coniferous forest between 1100 and 1650 m asl. These two forest cover types accounted for about 70% of the are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 0 publications
0
56
0
Order By: Relevance
“…The UNESCO Biosphere Reserve protects nearly 200 000 ha of natural vegetation and old-growth forest ecosystems. The reserve contains 1337 vascular plant species, including 1250 seed plant species (Xu 1992), and five vegetation zones (Wang et al 1980;Shao et al 1996) : broadleaf forest (below ' 700 m) , broadleaf-coniferous mixed forest (700-1 100 m) , coniferous forest (1 100-1700 m) , birch forest (1700-2100 m), and tundra (above 2100 m) (Figure 1). The coniferous forest zone, also called the dark coniferous forest or spruce-fir forest, is the dominant vegetation type inside the reserve (Li et al 1994;Shao et aL 1996).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The UNESCO Biosphere Reserve protects nearly 200 000 ha of natural vegetation and old-growth forest ecosystems. The reserve contains 1337 vascular plant species, including 1250 seed plant species (Xu 1992), and five vegetation zones (Wang et al 1980;Shao et al 1996) : broadleaf forest (below ' 700 m) , broadleaf-coniferous mixed forest (700-1 100 m) , coniferous forest (1 100-1700 m) , birch forest (1700-2100 m), and tundra (above 2100 m) (Figure 1). The coniferous forest zone, also called the dark coniferous forest or spruce-fir forest, is the dominant vegetation type inside the reserve (Li et al 1994;Shao et aL 1996).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Changbai Mountain in China has clear vertical vegetation zonation that ranges from mixed coniferous broadleaved forest at low altitude to alpine tundra above 2100 m (Shao et al 1996;Zhang et al 2011). In this study, we investigated the N and P concentrations of the leaves (N L , P L ), stems (N S , P S ) and fine roots (N R , P R ) along an altitudinal transect (500-2,300 m) on the northern slope of Changbai Mountain, China.…”
Section: Introductionmentioning
confidence: 99%
“…Now alpine tundra on Changbai Mountains is covered with abundant gramineous grasses, low shrubs or subshrubs, weeds, mosses and lichens [8]. Many studies have shown that in pioneer stages of succession, dominant species modify their environment in the short-or long-term, with effects on the vegetation dynamics [9]. Whereas the post-volcano successions have mainly been studied from a floristical and structural point of view, biomass or nutrients approaches to explain the vegetation dynamics are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients limitations are common during plant growth, especially for N and P. In general, biomass and soil nutrients change substantially with plant age. Biomass over time may differ among species, which is due to in part nutrients availability of different species over time [9,12]. P is the primary limiting nutrients in alpine tundra, although the degree of limitation varies markedly across the heterogeneous tundra landscape [13,14].…”
Section: Introductionmentioning
confidence: 99%